The women who threw corn: witchcraft and Inquisition in sixteenth-century Mexico - Nesvig, Martin Austin (Cambridge University Press, 2025)
This book tells the stories of women from Spain, North Africa, Senegambia, and Canaries accused of sorcery in sixteenth-century Mexico for adapting native magic and healing practices. These non-native women - the mulata of Seville who cured the evil eye; the Canarian daughter of a Count who ate peyote and mixed her bath water into a man's mustard supply; the wife of a Spanish conquistador who let her hair loose and chanted to a Mesoamerican god while sweeping at midnight; the wealthy Basque woman with a tattoo of a red devil; and many others - routinely adapted Native ritual into hybrid magic and cosmology. Through a radical rethinking of colonial knowledge, Martin Austin Nesvig uncovers a world previously left in the shadows of historical writing, revealing a fascinating and vibrant multi-ethnic community of witches, midwives, and healers.